ACTUAL PROBLEMS AND PROSPECTS FOR THE DEVELOPMENT OF ENVIRONMENTAL AUDIT IN THE REPUBLIC OF KAZAKHSTAN - K.M. Balginova,; G. Mussirov,; A.E. Shakharova,; S.R. Kalmagambetova,; B.B. Duisenbaeva, (Academic Journal of Physical and Chemical Sciences, 2019)
Any legal entity that is engaged in certain activities knows very well that in order to achieve success in its business, the correct distribution of financial resources and the most effective management are necessary. Therefore, for the proper development of the company and obtaining positive results, it is necessary to carry out certain actions in the work process that will allow you to find errors and problems in a timely manner. In short, the success of effective work lies in conducting a thorough and ongoing analysis of various data that directly relates to the entire work of the enterprise. Environmental audit should be focused on the internal individual needs of the enterprise in accordance with its policies and established goals.